Impact of metformin on statin‐associated myopathy risks in dyslipidemia patients - Keunhyeong Bak; Suhyeon Moon; Minjung Ko; Yeo Jin Choi; Sooyoung Shin (Wiley, 2023)
Abstract A growing number of patients with metabolic disorders are receiving statin and antidiabetic therapies as comedications. A signal of increased risk of myotoxicity due to potential interactions between antidiabetics and statins has been detected in previous studies. To investigate the effects of metformin on myopathy risks when added to preexisting statin therapy in dyslipidemia patients, we performed a retrospective cohort study using the Korean national health insurance data in statin‐treated dyslipidemia patients with or without concomitant metformin use. We compared the risk of myopathy in statin + metformin users against statin‐only users. Hazard ratios (HRs) and 95% confidence intervals (CIs) have been calculated following propensity score (PS) matching between study groups and subsequent stratification per patient factors. We included 4092 and 8161 patients in PS‐matched statin + metformin and statin‐only groups, respectively. The risk of myopathy decreased when metformin was used together with statins (adjusted HR 0.84; 95% CI 0.71-0.99). In subgroup analyses per individual statin agent and in stratified risk analyses, no specific statin agents or patient factors were associated with statistically significant myopathy risk. This study found that a comedication with metformin was associated with decreased myopathy risk in statin‐treated dyslipidemia patients compared to statin‐only users. Our findings suggest that metformin may provide protective effects on potential muscle toxicities induced by statin therapy.